Study on Hb H disease caused by the α2-globin gene initiation codon ATG > GTG mutation combined with Southeast Asian deletional α-thalassemia - Xiaobi LIU; Xuan XIAO; Hengying ZHU; Ping CHEN (Guangxi Yike Daxue xuebao, 2025)
Objective To explore the hemoglobin H (Hb H) diseases diseases caused by a rare α2-globin gene mutation combined with the Southeast Asian deletion of α -thalassemia gene mutation. Methods For the suspected cases of Hb H disease screened in the First Affiliated Hospital of Guangxi Medical University from January 2024 to December 2024, the fluorescent PCR melting curve analysis (FCMA) and gap-polymerase chain reaction (Gap-PCR) were used to detect the common non-deletional and deletional types of α-thalassemia gene mutations, and the DNA sequencing was utilized for rare mutation identification. Results Among 239 Hb H disease cases investigated, two cases with rare gene mutations were identified, and the genotype of these two cases was --SEA/αATG > GTGα. The familial cases originated from Nanning, Guangxi, and comprised a 33-year-old mother and her 6-year-old daughter. They had no history of jaundice, hepatosplenomegaly, or blood transfusion. The blood routine analysis showed that the red blood cell count (RBC) was 4.86-5.30×1012/L, Hb 91.0-92.0 g/L, the mean corpuscular volume (MCV) was 60.64-72.40 fL, and the mean corpuscular hemoglobin (MCH) was 17.24-18.90 pg. Hemoglobin analysis revealed that the percentage of Hb H was 20.5%-21.4%, and that of Hb Bart's was 9.8% -10.0%. Conclusion The Hb H disease caused by α2-globin gene initiation codon ATG > GTG mutation combined with the Southeast Asian deletional α-thalassemia was identified in the Guangxi region for the first time. Clinical presentation included mild anemia, and hemoglobin analysis showed the co-existence of Hb H and Hb Bart's. This gene mutation is rare and is prone to be overlooked in routine thalassemia gene testing, requiring gene sequencing for confirmation.